2002
DOI: 10.1108/13639510210437032
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the police

Abstract: This research updates and expands upon Decker’s article “Citizen attitudes toward the police: a review of past findings and suggestions for future policy” by summarizing the findings from more than 100 articles on perceptions of and attitudes toward the police. Initially, the value of research on attitudes toward the police is discussed. Then the research pertaining to the impact of individual level variables (e.g. race) and contextual level variables (e.g. neighborhood) on perceptions of the police is reviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
133
1
15

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 570 publications
(162 citation statements)
references
References 143 publications
(302 reference statements)
13
133
1
15
Order By: Relevance
“…Further, individuals living in residential neighborhoods tended to have more positive attitudes regarding police than respondents living elsewhere [17] . Some studies have found that rural residents view police less favorably than residents of urban areas [1] although there does not appear to be a consensus on this point. It is difficult to draw generalizations about neighborhoods, however, since people tend to cluster in neighborhoods with residents who have similar individual characteristics.…”
Section: Literature Reviewmentioning
confidence: 96%
See 3 more Smart Citations
“…Further, individuals living in residential neighborhoods tended to have more positive attitudes regarding police than respondents living elsewhere [17] . Some studies have found that rural residents view police less favorably than residents of urban areas [1] although there does not appear to be a consensus on this point. It is difficult to draw generalizations about neighborhoods, however, since people tend to cluster in neighborhoods with residents who have similar individual characteristics.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Brown and Benedict [1] pointed out that while many studies have identified neighborhood differences, "there is no consensus about why attitudes towards the police vary by neighborhood." Kusow, Wilson and Martin [19] , found that the most powerful predictor of satisfaction with police was "race-residential location."…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…I de fleste tilfeller synes imidlertid effekten av disse variablene å vaere moderat, saerlig etter kontroll for andre relevante variabler (Brown & Benedict, 2002;Thomassen, 2010).…”
Section: Teori Og Tidligere Forskningunclassified